A MD Simulation and Analysis for Aggregation Behaviors of Nanoscale Zero-Valent Iron Particles in Water via MS. (27th August 2014) - Zhao, Ying; Liu, Dongmei; Tang, Huan; Lu, Jing; Cui, Fuyi
Abstract : With the development of nanotechnology, more nanomaterials will enter into water environment system. Studying the existing form of nanomaterials in water environment will help people benefit from the correct use of them and to reduce the harm to human caused by them for some nanomaterials can bring polluting effect. Aggregation is a main behavior for nanoparticle in water environment. NZVI are used widely in many fields resulting in more NZVI in water environment. Molecular dynamics simulations and Materials Studio software are used to investigate the microaggregation behaviors of NZVI particles. Two scenes are involved: (1) particle size of NZVI in each simulation system is the same, but initial distance of two NZVI particles is different; (2) initial distance of two NZVI particles in each simulation system is the same, but particle size of NZVI is different. Atomistic trajectory, NP activity, total energy, and adsorption of H2 O are analyzed with MS. The method provides new quantitative insight into the structure, energy, and dynamics of the aggregation behaviors of NZVI particles in water. It is necessary to understand microchange of NPs in water because it can provide theoretical research that is used to reduce polluting effect of NPs on water environment.